Enhanced Uptake of Processed Bovine β-Lactoglobulin by Antigen Presenting Cells: Identification of Receptors and Implications for Allergenicity - Teodorowicz, Malgorzata; Zenker, Hannah E.; Ewaz, Arifa; Tsallis, Theodoros; Mauser, Andreas; Gensberger-Reigl, Sabrina; de Jong, Nicolette W.; Hettinga, Kasper A.; Wichers, Harry J.; van Neerven, R. J.Joost; Savelkoul, Huub F.J. (Molecular Nutrition & Food Research, 2021)
Scope: β-lactoglobulin (BLG) is a major cow milk allergen encountered by the immune system of infants fed with milk-based formulas. To determine the effect of processing on immunogenicity of BLG, this article characterized how heated and glycated BLG are recognized and internalized by APCs. Also, the effect of heat-induced structural changes as well as gastrointestinal digestion on immunogenicity of BLG is evaluated. Methods and results: The binding and uptake of BLG from raw cow milk and heated either alone (BLG-H) or with lactose/glucose (BLG-Lac and BLG-Glu) to the receptors present on APCs are analyzed by ELISA and cell-binding assays. Heated and glycated BLG is internalized via galectin-3 (Gal-3)and scavenger receptors (CD36 and SR-AI) while binding to the receptor for advanced glycation end products (R AGE) does not cause internalization. Receptor affinity of BLG is dependent on increased hydrophobicity, β-sheet exposure and aggregation. Digested glycated BLG maintained binding to sRAGE and Gal-3 but not to CD36 and SR-AI, and is detected on the surface of APCs. This suggests a mechanism via which digested glycated BLG may trigger innate (via RAGE) and adaptive immunity (via Gal-3). Conclusions: This study defines structural characteristics of heated and glycated BLG determining its interaction with APCs via specific receptors thus revealing enhanced immunogenicity of glycated versus heated BLG.
CRIS-Team Scopus Importer:2021-03-19
Keywords: aggregation of β-lactoglobulin; cow milk processing; digestion of β-lactoglobulin; galactin-3 Maillard reaction ligands; glycation of β-lactoglobulin; RAGE Maillard reaction ligands